Deep neck space infections: a study of 20 cases - Save, Sneha L. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2023)
Background: Deep neck space infections is defined as infection in the potential spaces and fascial planes of the neck. Deep location and complexity of these spaces make diagnosis and treatment difficult. Proper diagnosis and immediate treatment is necessary to attain cure without any complications. Treatment principally comprises of airway management, surgical intervention i. e.; incision and drainage of the abscess and appropriate antibiotic treatment as per culture and sensitivity report. Methods: Present study was performed from June 2015 to June 2016 and comprised of 20 cases. All patients coming to the OPD of tertiary care centre with suspected deep neck space infections. The demographic characteristics, presenting symptoms, etiology, imaging and treatment of each case was reviewed. Results: We evaluated 20 patients with deep neck space infections. The mean age was found to be 40 years. Diabetes was found to be a co-morbid condition in 25% of the patients. Male: female ratio was 1:1.5. In the majority of cases, the etiological factor was found to be odontogenic infections (50%). Streptococcus pyogenes was the organism which was most commonly isolated. Ludwig’s angina was the most common clinical presentation (20%). Conclusions: Deep neck space infection is a life-threatening condition in diabetics, immune-compromised and elderly patients. Odontogenic infections were the most common etiology for deep neck space infections. There is need to establish secure airway before initiating surgical intervention. The widespread use of antibiotics has decreased the incidence of deep neck space infections, but remains a fairly common problem.